Teaching Data Literacy for Civic Engagement: Resources for Data Capture and Organization - Locke, Brandon; Heppler, Jason (KULA, 2018)
Endangered Data Week emerged in the early months of 2017 as an effort to encourage conversations about government-produced, open data and the many factors that can limit its access. The event offers an internationally-coordinated series of events that includes publicizing the availability of datasets, increasing critical engagement with them, encouraging open data policies at all levels of government, and the fostering of data skills through workshops on curation, documentation and discovery, improved access, and preservation. The reflection provides an outline of the curriculum development happening through Endangered Data Week and encourages others to contribute.